Targeting clinically-relevant metallo-β-lactamases: from high-throughput docking to broad-spectrum inhibitors. (1st November 2016) - Brindisi, Margherita; Brogi, Simone; Giovani, Simone; Gemma, Sandra; Lamponi, Stefania; De Luca, Filomena; Novellino, Ettore; Campiani, Giuseppe; Docquier, Jean-Denis; Butini, Stefania
Abstract: Metallo-β-lactamases (MBLs) represent one of the most important and widespread mechanisms of resistance to β-lactam antibiotics (including the life-saving carbapenems), against which no clinically useful inhibitors are currently available. We report herein a structure-based high-throughput docking (HTD) campaign on three clinically-relevant acquired MBLs (IMP-1, NDM-1 and VIM-2). The initial hit NF1810 (1 ) was optimized providing the broad-spectrum inhibitor3i, which is able to potentiate the in vitro activity of cefoxitin on a VIM-2-producing E. coli strain.